Professional activity of people with epilepsy - Anna Staniszewska; Marcin Sobiecki; Aneta Duda-Zalewska; Urszula Religioni; Grzegorz Juszczyk; Tomasz Tatara; Robert Słoniewski (Nofer Institute of Occupational Medicine, 2015)
Background: The aim of the study was to determine the occupational activity of epileptic patients. Particular attention was paid to employment of people with epilepsy, the way the workplace is informed about the disease, impact of education on employment opportunities and the relationship between clinical type of epilepsy and professional activity. Material and Methods: Patients were recruited from the neurological outpatient clinic in Warszawa and asked to fill in a customized questionnaire, containing questions on their socio-demographic, clinical and employment status. Results: The study included 197 adult patients with epilepsy (64 professionally active and 133 inactive). As many as 47.7% of respondents declared that the disease impeded their employment, and 77.2% admitted that the occurrence of seizure at work had negatively affected their comfort. As many as 42.2% professionally active respondents had revealed the disease at work. There was a statistically significant difference between individuals with primarily generalized seizures and those with partial and secondarily generalized seizures (30.61% vs. 2.63%, p < 0.05). Education had also a significant positive impact on employment (47.06% employed with university degree vs. 9.76% with primary education, p < 0.05). No significant correlations between duration of the disease or number of the epileptic seizures, independent of their type and revealing the disease in the workplace, were observed (p > 0.05). Neither current work status had impact on opinions about difficulties in finding a job (p > 0.05). Conclusions: Epilepsy is a great obstacle to finding and maintaining employment. Less than 1/2 of patients inform the workplace about their illness, mainly due to previous negative experiences. Since education significantly enables the employment, programs aimed at promoting vocational activation of patients should facilitate access to learning. Med Pr 2015;66(3):343-350